Parasitic nematodes : molecular biology, biochemistry, and immunology - Kennedy, M. W. (Malcolm W.); Harnett, W. (William) (CABI Pub., 2001)
This book covers recent advances made in the genetics and biochemistry of nematodes, and the immunology of infections which have been made possible by new molecular genetic, biochemical and immunological tools. The topics covered include: molecular analysis of nematode evolution; Wolbachia endosymbionts of filarial nematodes; genetic analysis of plant-parasitic nematode-host interactions; identification of parasitic nematodes and study of genetic variability using PCR approaches; diversity in populations of parasitic nematodes and its significance; host modulation and manipulation; new insights into the intestinal niche of Trichinella spiralis; genetic reprogramming of mammalian skeletal muscle cells; plant-parasitic nematodes; synthesis, modification and mutants of the nematode cuticle; chitinases of filarial nematodes; acetylcholinesterase secretion by nematodes; genes, protein structure and function of the surface and secreted antigens of Toxocara canis; nematode gut peptidases, proteins and vaccination; metabolic transitions and the role of the pyruvate dehydrogenase complex during development of Ascaris suum; novel carbohydrate structures; structurally novel lipid-binding proteins; T-helper cell cytokine responses during intestinal nematode infection; gut immunopathology in helminth infections; immunomodulation by filarial nematode phosphorylcholine-containing glycoproteins; nematode neuropeptides; and neurobiology of nematode muscle.